2012
DOI: 10.1007/s12402-012-0083-5
|View full text |Cite
|
Sign up to set email alerts
|

To what extent are task-switching deficits in children with attention-deficit/hyperactivity disorder independent of impaired inhibition?

Abstract: Executive functions, higher-order cognitive functions needed for goal-directed behavior, have been studied extensively in the search for endophenotypes for ADHD, yet results have been inconclusive. We examine the performance of children with ADHD in task switching as an as yet understudied potential endophenotype. A group of 20 children with ADHD and a group of 23 children without ADHD (ages 7-12) performed a task-switching paradigm and a Go/No-Go Task. Children with ADHD displayed significantly greater specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Identifying deficits in executive functioning constitutes a major challenge in clinical (neuro)psychology. It has been criticized, in this connection, that commonly used procedures are characterized by lack of theoretical justification and more specific assessment of separable components of executive functions are desirable [ 40 , 41 ] This seems to apply, particularly, to task switching performance as a diagnostic means, which has been found to be impaired in ADHD in some previous studies [ 8 , 11 , 15 ] but has been associated with comparably low effect sizes in meta-analyses [ 1 , 42 ] Alongside with the search for discriminative subtypes in ADHD [ 43 ], isolating more specific components of task-set shift, as attempted in the current study with regard to shifting the attentional set, seems a valuable method to improve this situation, and allows a more detailed description of which cognitive processes may be affected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying deficits in executive functioning constitutes a major challenge in clinical (neuro)psychology. It has been criticized, in this connection, that commonly used procedures are characterized by lack of theoretical justification and more specific assessment of separable components of executive functions are desirable [ 40 , 41 ] This seems to apply, particularly, to task switching performance as a diagnostic means, which has been found to be impaired in ADHD in some previous studies [ 8 , 11 , 15 ] but has been associated with comparably low effect sizes in meta-analyses [ 1 , 42 ] Alongside with the search for discriminative subtypes in ADHD [ 43 ], isolating more specific components of task-set shift, as attempted in the current study with regard to shifting the attentional set, seems a valuable method to improve this situation, and allows a more detailed description of which cognitive processes may be affected.…”
Section: Discussionmentioning
confidence: 99%
“…Daily life difficulties experienced by individuals suffering under ADHD symptoms have frequently been linked to deficits in executive functions, a class of mental processes assumed to organize cognitive activity in the service of goal-directed behavior (e.g., [ 1 8 ]). Although the concept of executive functions is not well defined, a core aspect thereof relates to the ability to adjust mental sets according to changing task requirements and context conditions.…”
Section: Introductionmentioning
confidence: 99%
“…I doubt this conclusion and will suggest one challenging fact: the increased switch cost observed in attention deficits. This finding that has been replicated several times, including a related finding of “normalization” of switch costs under methylphenidate treatment ( Kramer, Cepeda, & Cepeda, 2001 ; Luna-Rodriguez, Wendt, Kerner auch Koerner, Gawrilow, & Jacobsen, 2018 ; Rauch, Gold, & Schmitt, 2012 ). Given how attention deficits are defined by the DSM ( American Psychiatric Association, 2013 ), it is difficult to attribute the increased switch cost and its “normalization” to features that are completely unrelated to cognitive control.…”
mentioning
confidence: 72%
“…Using the same task, Cepeda et al (2000) and Kramer et al (2001) reported larger switch costs in those with ADHD compared to controls while Oades and Christiansen (2008) failed to find a significant difference in switch costs. Other studies reported significantly larger switch costs for ADHD participants (King, Colla, Brass, Heuser, & von Cramon, 2007) while others did not (Rauch, Gold, & Schmitt, 2012). For example, Wu et al (2006) investigated the switching performance for those with and without ADHD under WM load.…”
Section: Task Switching and Adhdmentioning
confidence: 99%